RANCANG BANGUN DATA WAREHOUSE PADA KANTOR DINAS PENDIDIKAN DAN PENGAJARAN KABUPATEN MERAUKE - , Maurits Jacobus Pongliku ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Data and information are the important assets in many activities, including educational ones. Office of Education in Merauke, recently there are some systems to support the need of data and information on educational environment, however, one system to another are not in a single entity, therefore they are not able to provide data and information quickly and integrated. A technology need to integrated data and information, and this technology called the data warehouse. Data Warehouse is a relational databases to query and analyze, not for transaction process. It can save and process a lot of data from many sources, then integrate them to be analized. The purpose of this research is to find how to integrate the whole studentâs data which are spread in differents schools into the data warehouse. Logical model data of data warehouse in this research use the star schema, which can show the relation in each table as dimension and measure that, will figure out the informational needed and to answer the question from the user. The analysis of the data warehouse using OLAP (On-Line Analytical Processing), to analyze the student score and data at Office of Education in Merauke. The result show that the multidimensional data is designed to analyze the average score of national examination of studentâs perspective, schoolâs type, schoolâs level, school`s status, and the number of students based on schoolâs name, school`s status, school`s type, schoolâs level, student`s gender, and ethnic. The multidimensional data analysis (OLAP) consist of Contourcube component , that can operate a rotation/pivoting, filtering, sorting, slicing/dicing, and drill-down/drillup, and allows the user to analyze from different point of view with an output graphic display created by user.